2013
DOI: 10.1093/mnras/stt049
|View full text |Cite
|
Sign up to set email alerts
|

The relation between velocity dispersion and mass in simulated clusters of galaxies: dependence on the tracer and the baryonic physics

Abstract: We present an analysis of the relation between the masses of cluster-and group-sized halos, extracted from ΛCDM cosmological N-body and hydrodynamic simulations, and their velocity dispersions, at different redshifts from z = 2 to z = 0. The main aim of this analysis is to understand how the implementation of baryonic physics in simulations affects such relation, i.e. to what extent the use of the velocity dispersion as a proxy for cluster mass determination is hampered by the imperfect knowledge of the baryon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
335
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 256 publications
(401 citation statements)
references
References 65 publications
61
335
5
Order By: Relevance
“…Numerical simulations confirmed that the σv-M∆ relation is consistent with the self-similar scaling with mass (Evrard et al 2008;Munari et al 2013;Saro et al 2013). Some differences may arise from the galaxy population used to estimate the velocity dispersion and from the impact of selection using galaxy colour, projected separation from the cluster centre, galaxy luminosity, and spectroscopic redshift (Saro et al 2013).…”
Section: σV-m∆supporting
confidence: 64%
See 2 more Smart Citations
“…Numerical simulations confirmed that the σv-M∆ relation is consistent with the self-similar scaling with mass (Evrard et al 2008;Munari et al 2013;Saro et al 2013). Some differences may arise from the galaxy population used to estimate the velocity dispersion and from the impact of selection using galaxy colour, projected separation from the cluster centre, galaxy luminosity, and spectroscopic redshift (Saro et al 2013).…”
Section: σV-m∆supporting
confidence: 64%
“…This is the approach usually followed in numerical simulations (Evrard et al 2008;Munari et al 2013;Saro et al 2013) to built mass proxies based on the velocity dispersion without assuming dynamical equilibrium and without exploiting the properties of the infall patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For haloes without these effects, the velocity dispersion profiles are isothermal and isotropic as in Paper I, with a velocity dispersion that depends on halo mass and radius through the scaling σ 2 200 = 1 2 GM200/R200 (but see Mamon et al 2010;Munari et al 2013;Old et al 2013). The updated model, including a more realistic velocity dispersion profile and an anisotropy model, will be described in Skibba (in preparation).…”
Section: Halo Occupation Distribution Modelmentioning
confidence: 97%
“…This method is used (e.g. Carlberg, Yee & Ellingson 1997;Biviano & Poggianti 2009;Munari et al 2013;Rines et al 2013) when the number of spectroscopic members per cluster is low and does not allow accurate, individual, velocity dispersion measurements. Becker et al (2007), in particular, could measure with accuracy the relation between optical richness and velocity dispersion of optically selected galaxy clusters up to z = 0.3 by means of stacking systems in richness and redshift.…”
Section: Cluster L X -σ Relation From Stacked Velocity-distance Diagramsmentioning
confidence: 99%